Sex differences in connexin-43 expression in left ventricles of aging rats - Tribulová, N; Dupont, E; Soukup, T; Okruhlicová, L; Severs, N J (Physiological research, 2005)
Cardiac gap junctions have been implicated in maintaining intercellular electrical and metabolic couplings. The abnormalities in connexin-43 (Cx43) lead to conduction defects and contractile dysfunction. We have evaluated the expression and phoshorylation status of Cx43 in the left ventricular myocardium of male and female 16-month-old rats submitted to 14-week L-thyroxine (T4) treatment. Western blot analysis revealed the presence of fully or intermediately phosphorylated and unphosphorylated forms of Cx43. We have found no significant differences in Cx43 expression and phosphorylation between T4-treated and control untreated animals. However, expression of Cx43 was significantly higher in female compared to male rats. We conclude that T4 administration has no effect on Cx43 expression, but there are sex-dependent differences in Cx43 expression in the left ventricles between aging male and female rats.
Keywords: Sex Factors; Phosphorylation; Connexin 43; fosforylace; konexin 43; Female; stárnutí; krysa rodu Rattus; zvířata; Aging; potkani Wistar; sexuální faktory; ženské pohlaví; Rats, Wistar; Male; Heart Ventricles; Rats; myokard; Animals; Myocardium; mužské pohlaví; srdeční komory